Integrated halal supply chain system in food manufacturing industry - Sulaiman, Shamsuddin; Aldeehani, A.; Aziz, F. A.; Mustapha, F. (ISLAMIC WORLD Network for Environmental Science and Technology (IWNEST PUBLICATION), 2018)
This paper presents the development of integrated model of halal supply chain, one of most fundamental part in halal food manufacturing industries. The market of halal products is widely distributed throughout the world. There is global increase in the demand for halal products by Islamic countries as well as by non-Islamic countries. Halal food consumers are presently more alert and concern about the integrity of Halal status. Furthermore, they also curious about all the activities involved along the supply chain whether the products that they purchased were truly halal from the beginning to the end. The need of halal supply chain is crucial in ensuring that the concept of halal is not only applicable for the food itself but also for the whole supply chain starting from the farm to the customer. This project attempts to develop an integrated halal supply chain system that can be used by food manufacturers that are developing halal products for better productivity and quality. The identified supply chain components are human resources, process, environment, accreditations, logistics and traceability.